Multimodal assessment of SERS nanoparticle biodistribution post ingestion reveals new potential for clinical translation of Raman imaging. (August 2017) - Campbell, Jos L.; SoRelle, Elliott D.; Ilovich, Ohad; Liba, Orly; James, Michelle L.; Qiu, Zhen; Perez, Valerie; Chan, Carmel T.; de la Zerda, Adam; Zavaleta, Cristina
Abstract: Despite extensive research and development, new nano-based diagnostic contrast agents have faced major barriers in gaining regulatory approval due to their potential systemic toxicity and prolonged retention in vital organs. Here we use five independent biodistribution techniques to demonstrate that oral ingestion of one such agent, gold-silica Raman nanoparticles, results in complete clearance with no systemic toxicity in living mice. The oral delivery mimics topical administration to the oral cavity and gastrointestinal (GI) tract as an alternative to intravenous injection. Biodistribution and clearance profiles of orally (OR) vs. intravenously (IV) administered Raman nanoparticles were assayed over the course of 48 h. Mice given either an IV or oral dose of Raman nanoparticles radiolabeled with approximately 100 μCi (3.7MBq) of 64 Cu were imaged with dynamic microPET immediately post nanoparticle administration. Static microPET images were also acquired at 2 h, 5 h, 24 h and 48 h. Mice were sacrificed post imaging and various analyses were performed on the excised organs to determine nanoparticle localization. The results from microPET imaging, gamma counting, Raman imaging, ICP-MS, and hyperspectral imaging of tissue sections all correlated to reveal no evidence of systemic distribution of Raman nanoparticles after oral administration and complete clearance from the GI tract within 24 h. Paired with the unique signals and multiplexing potential of Raman nanoparticles, this approach holds great promise for realizing targeted imaging of tumors and dysplastic tissues within the oral cavity and GI-tract. Moreover, these results suggest a viable path for the first translation of high-sensitivity Raman contrast imaging into clinical practice.